Carboxylic Acid Initiated Organocatalytic Ring-Opening Polymerization of N‑Sulfonyl Aziridines: An Easy Access to Well-Controlled Polyaziridine-Based Architectural and Functionalized Polymers - Yang, Ruhan; Wang, Ying; Luo, Wenyi; Jin, Yaocheng; Zhang, Zhen; Wu, Chuande; Hadjichristidis, Nikos (Macromolecules, 2019)
A highly easy and efficient metal-free methodology for the synthesis of polyaziridine-based polymers with controlled architectures and desired functionalities was developed by organocatalytic ring-opening polymerization (ROP) of N-sulfonyl aziridines with a carboxylic acid as initiator. 1,5,7-Triazabicyclo[4.4.0]dec-5-ene (MTBD) and phosphazene t-Bu-P4 organocatalysts have demonstrated high catalytic efficiency in connection with the controlled/living character of the ROP of 2-methyl-N-tosylaziridines (TsMAz) initiated by benzoic acid. Aryl carboxylic acids bearing an azido or a hydroxyl group as well as bio-derived vanillic acid and syringic acid and alkyl- and alkenyl-substituted carboxylic acids, such as acetic acid, palmitic acid, and methacrylic acid, can all initiate the ROP of TsMAz toward well-defined P(TsMAz)s. α,ω-Diamino telechelic, star-shaped P(TsMAz)s, and poly(styrene-co-methacrylic acid)-graft-poly(2-methyl-N-tosylaziridine) [P(St-co-MAA)-g-P(TsMAz)] have been conveniently synthesized from the corresponding multicarboxyl (macro)initiators. Finally, this protocol has been applied for the synthesis of a linear photoresponsive P(TsMAz) and an aggregation-induced emission (AIE)-active 4-arm P(TsMAz) star from the corresponding functionalized carboxylic acids.